STRATEGI BERTAHAN HIDUP RUMAH TANGGA NELAYAN TRADISIONAL DI DESA BANGKO PUSAKA KECAMATAN BANGKO PUSAKO KABUPATEN ROKAN HILIR - Jufri "; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was motivated by the economic life of fishermen in Bangko village. Traditional fishermen's heritage using only canoes and paddles to find fish was not able to compete with modern fishermen who used motorized boats and sophisticated fishing gear. Their low income due to the limited economic education and and lack of capital theory used by survival strategy theory researchers used qualitative research in which respondents were selected according to the criteria determined by the traditional fishermen, namely active, passive and network strategies. . Traditional fishermen in the village of BangkoPusaka also have side jobs such as gardening, taking wages, savings, and debt. And then the reason fishermen continue to work as traditional fishermen is because of the low education of these fishermen, the difficulty of finding work. Keywords: Traditional Fishermen, Survival Strategy